1997
DOI: 10.1128/jb.179.6.1940-1945.1997
|View full text |Cite
|
Sign up to set email alerts
|

UV-B-induced synthesis of photoprotective pigments and extracellular polysaccharides in the terrestrial cyanobacterium Nostoc commune

Abstract: Liquid cultures of the terrestrial cyanobacterium Nostoc commune derived from field material were treated with artificial UV-B and UV-A irradiation. We studied the induction of various pigments which are thought to provide protection against damaging UV-B irradiation. First, UV-B irradiation induced an increase in carotenoids, especially echinenone and myxoxanthophyll, but did not influence production of chlorophyll a. Second, an increase of an extracellular, water-soluble UV-A/B-absorbing mycosporine occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
180
7
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(192 citation statements)
references
References 40 publications
4
180
7
1
Order By: Relevance
“…Cyanobacteria may need two cyclases to regulate production of mono-and dicyclic carotenoids independently. Myxoxanthophyll has been shown to accumulate in cyanobacteria in response to UV radiation while ␤-carotene levels remain constant (59,60). Independent regulation of these genes may also explain the phenotypes of the cruP and cruA mutants.…”
Section: Discussionmentioning
confidence: 97%
“…Cyanobacteria may need two cyclases to regulate production of mono-and dicyclic carotenoids independently. Myxoxanthophyll has been shown to accumulate in cyanobacteria in response to UV radiation while ␤-carotene levels remain constant (59,60). Independent regulation of these genes may also explain the phenotypes of the cruP and cruA mutants.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that periphytic EPS in our study system was relatively more resistant to UV degradation, or that any UV-induced degradation of EPS was offset by increased periphytic biomass or EPS production. For example, UV exposure cues the cyanobacterium Nostoc commune to produce additional EPS, possibly to serve as a photoprotective compound (Ehling-Schulz et al 1997). It should also be noted that the Paint Creek wetland experienced a heavy rain event and a subsequent increase in water level <12 h prior to the day 3 1 sampling.…”
Section: Resultsmentioning
confidence: 99%
“…In another epipelon study, EPS was reduced in +W plots as compared to -UV plots, but only on a few sample days (Roux et al 2002). In contrast, glycan-rich EPS production increased significantly in the cyanobacterium Nostoc commune under laboratory exposures to UV-B but not UV-A (Ehling-Schulz et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies on the influence of light intensity (Friedman et al, 1991;Moreno et al, 1998;Otero and Vincenzini, 2003;Trabelsi et al, 2009;Yu et al, 2010;Mota et al, 2013) and wavelengths (Ehling-Schulz et al, 1997;Chen et al, 2009) on EPS yield have been reported. Different light regimens (continuous light and light-dark cycles) do not significantly affect the monosaccharidic composition of EPS (Vincenzini et al, 1993;De Philippis and Vincenzini, 1998).…”
mentioning
confidence: 99%